Eksplorasi Etnomatematika dalam Gerakan Pencak Silat PSHT dari Madiun - Lutfi Tafrikhan (JUMAT: Jurnal Matematika, 2025)
Martial Art is one of the legacies of the ancestors of the Indonesian people which developed from the kingdom era to the present. Pencak Silat is a very popular martial art. One of them is Pencak Silat from the Faithful Heart Terate Brotherhood (PSHT). The aim of this research is to explore ethnomathematics in the PSHT Pencak Silat movement with a focus on geometric concepts. This research uses descriptive qualitative research. Data was collected through interviews with sources from one of the PSHT members, observation and documentation. The results obtained show that angle concepts such as obtuse angles, acute angles and right angles are present in PSHT Pencak Silat movements. Apart from that, the concept of straight line geometry was also discovered.